Assembly of 1D coaxial nanoribbons into 2D multicolor luminescence array membrane endowed with tunable anisotropic electrical conductivity and magnetism via electrospinning. Issue 52 (27th June 2017) - Shao, Hong; Yu, Wensheng; Ma, Qianli; Wang, Xinlu; Dong, Xiangting; Liu, Zhelin; Wang, Jinxian; Liu, Guixia; Chang, Limin
Abstract : A flexible 2D color-tunable coaxial nanoribbon array membrane with anisotropic electrical conductivity and magnetism is successfully fabricated via one-pot electrospinning. Abstract : A flexible 2D color-tunable coaxial nanoribbon array membrane with anisotropic electrical conductivity and magnetism assembled by 1D coaxial nanoribbons is obtained via coaxial electrospinning technology using a specially designed coaxial spinneret. Each coaxial nanoribbon in the array is composed of an Fe3 O4 nanoparticle (NPs)/polymethyl methacrylate (PMMA) magnetic core and [Eu(TTA)3 (TPPO)2 + Tb(TTA)3 (TPPO)2 ]/polyaniline (PANI)/PMMA [TTA = 2-thenoyltrifluoroacetone radical, TPPO = tris( N, N -tetramethylene)phosphoric acid triamide] conductive photoluminescent shell, and the array membrane is formed by aligned coaxial nanoribbons. Tunable colors ranging from green to red can be achieved in the coaxial nanoribbon array membrane by modulating the mass ratio of Eu(TTA)3 (TPPO)2, Tb(TTA)3 (TPPO)2, PANI and Fe3 O4 NPs. Additionally, other functions such as magnetism and anisotropic electrical conductivity are conveniently exhibited by the coaxial nanoribbon array membrane to realize multifunctionality. The ratio of the conductivity parallel and perpendicular to the length direction of the nanoribbons is as high as five due to the unique nanostructure of the array membrane. Also, the magnetic performance, electrical conductivity and electrically conductive anisotropy of the coaxial nanoribbon array membrane can be tuned by modulating the contents of PANI and Fe3 O4 NPs. The coaxial nanoribbon array membrane exhibits a much better luminescent performance and electrically conductive anisotropy than its counterpart composite nanoribbon array membrane. Furthermore, the design philosophy and synthetic method for the flexible coaxial nanoribbon array membrane provide a new and facile strategy for the preparation of color-tunable 2D nanomaterials with multifunctionality.